Ginkgo biloba Extract 50 (GBE50) Ameliorates Insulin Resistance, Hepatic Steatosis and Liver Injury in High Fat Diet-Fed Mice - Li L (Dove Medical Press, 2021)
Liu Li,1,* Li Yang,1,* Feng Yang,2,* Xin-lan Zhao,1 Shengjiang Xue,3 Fang-hua Gong4 1No.2 Department of Endocrinology, Hunan Provincial People’s Hospital, The First Affiliated Hospital of Hunan Normal University, Changsha, 410002, People’s Republic of China; 2No.2 Department of Pharmacy, Hunan Provincial People’s Hospital, the First Affiliated Hospital of Hunan Normal University, Changsha, 410002, People’s Republic of China; 3Ladder Molecular Biomedical Research Center, Guangzhou, 510800, People’s Republic of China; 4Department of Nursing, Hunan Provincial People’s Hospital, the First Affiliated Hospital of Hunan Normal University, Changsha, 410002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shengjiang XueLadder Molecular Biomedical Research Center, No. 39 Zhanqian Road, Xinhua Street, Huadu District, Guangzhou, 510800, People’s Republic of ChinaEmail wsjiangzi@126.comFang-hua GongDepartment of Nursing, Hunan Provincial People’s Hospital, the First Affiliated Hospital of Hunan Normal University, No. 61 Jiefangxi Road, Furong District, Changsha, 410002, Hunan Province, People’s Republic of ChinaTel +86 0731-84762691Fax +86 0731-8329065Email gfhnurse@aliyun.comBackground: Ginkgo biloba extract 50 (GBE50) has a variety of pharmacological functions such as anti-inflammatory, antioxidant and maintenance of glucose and lipid metabolism homeostasis. However, the therapeutic effects and mechanisms of GBE50 on non-alcoholic fatty liver disease (NAFLD) remain unknown. Therefore, in this study, we evaluated the therapeutic effects of GBE50 in NAFLD by using a high-fat diet (HFD) mice model.Methods: C57BL/6J mice were fed a HFD diet for 15 weeks and were given respectively 25, 50, and 100 mg/kg GBE50 daily by gavage from 3 to 15 weeks. After the administration, blood samples and liver tissues were collected for biochemical detection, histological measurement, immunohistochemistry and Western blot, respectively.Results: We found that GBE50 treatment could ameliorate insulin resistance (IR), glucose intolerance, lipid accumulation, hepatic steatosis and liver injury in HFD-fed mice. Further mechanism exploration discovered that the hepatoprotective effects of GBE50 on NAFLD may be related to the strengthening of IRS-1 signal activation and the weakening of NF-κB, Akt and endoplasmic reticulum stress signals activation.Conclusion: GBE50 is a potentially powerful therapeutic agent for the treatment of NAFLD.Keywords: Ginkgo biloba extract 50, non-alcoholic fatty liver disease, insulin resistance, hepatic steatosis, inflammatory response, liver injury